Area Reduction Of Syndrome Calculator For Strong Bose-Chaudhuri-Hocquenghem Decoder - Koay , Kim Leong (2016)

(untitled)
Bose–Chaudhuri–Hocquenghem (BCH) codes have a widespread use to provide the error protection for multiple random errors in a binary code. BCH codes is commonly applied in various practical application such as advanced solid-state drives (SSDs), high-speed fiber optical communications system and wireless communication system. The operation in a BCH decoder can be summarized into 3 steps: 1) compute the syndromes from the received codeword; 2) computing the error locator polynomial; 3) locating the errors. This research project proposed an area efficient Syndrome Calculator block of the BCH (n=255, k=111, t=18) decoder. In the previous SC block architecture, all the odd-index syndromes need to be computed by direct calculation which consume more area. In the current proposed architecture, Galois field’s property is exploited to compute the odd-index syndromes by using power operation in order to save the area consumption. This architecture is better in terms of area compared with previous architecture. In conclusion, by computing the odd-index syndromes with power operation, 8% area saving is achieved without compromising the power consumption and its operating frequency.